DESIGNING A COMPUTER BASED TEST VERSION OF A VOCABULARY TEST - Safriyani, Rizka (English Education Department STKIP Al Hikmah Surabaya, 2019)
This research aims to design A Computer Based Test Version of An Academic Vocabulary Test. This study is intended to portray students' capacity in understanding Academic Vocabulary. Also, this research also describes the student's perception of the utilization of the computer-based test.  In this study, media and material specialist were involved to confirm the content validity and product quality. Other than that, there are 50 learners participated as the test taker. Surveys and Academic Vocabulary Test was done to resemble the data. Evaluation regarding the program was completed concerning material and the aspects of the media. The suggestion given by the expert were utilized to enhance the utilization of the computer-based test. The validator recommends utilizing four steps; creating interface, coding, publishing, and packaging. Moreover, after the utilization of Computer Based Test, the English Teacher Education Department students' capacity in understanding the meaning of Academic Vocabulary is known in the average level. They have got the average mean score of 53 forthe vocabulary test. On the other hand, the result of non-English Teacher Education Department students'capacity in doing the test is in the low level. They have got the average mean score of 35 forthe vocabulary test. Moreover, the student's opimiom shows that there are 95,5% of the students provide a positive perception to the utilization of A Computer Based Test. They feel positive because of the practicality, and the particular effectiveness of the program to describe students' capacity in understanding Academic Vocabulary.